If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x(6-7)7=13
We simplify the equation to the form, which is simple to understand
5x(6-7)7=13
Reorder the terms in parentheses
+(-5x)*7=13
Reorder the terms in parentheses
+(-35x)=13
Remove unnecessary parentheses
-35x=+13
We move all terms containing x to the left and all other terms to the right.
-35x=+13
We simplify left and right side of the equation.
-35x=+13
We divide both sides of the equation by -35 to get x.
x=-0.37142857142857
| 7(x-3)+3(4-3)=-8 | | [(1)(2)](3)=[(2)(1)](3) | | 0=(2x-4):(x+1) | | X+1(29)3x= | | y=1.5+1.5x | | n^2=-2n+8 | | 29*6= | | y=1.5+1.5y | | x+12=3x-18 | | 5(4x-2)+3=11 | | 0=X^2+8x+2 | | 9x-7/8=7 | | -20=-4k-6k | | -8y=-12-12x | | 9t-9=32-4t+24 | | 20tan^2x=3+9sec^2x | | Sec^2x=1+tan^2x | | 0=2x^2-8x+5 | | 2-x=3x+2 | | 3x+1=6-2x | | 4+x=3+0.5x | | 1y+8=7 | | 0.70*x=8000 | | r+23.57=30 | | 20x^2-33x^2-67x-24/5x-3 | | 2(t-3)=4-3t | | 5/4=8/x | | y+17=2y | | 2y+9y=0 | | 5x-1=3(x-7)+4 | | S-8.4=11.3 | | 2=a |